Celowość stosowania rachunku kosztów działań (Activity-Based Costing) w zarządzaniu w służbie zdrowia - Banasiewicz, Kazimierz; Nawara, Paweł (Activity-Based Costing as a Proper Mean in Practice of Healthcare Management, 2006)
Activity-Based Costing (ABC) is an accounting technique that allows an organization to determine the actual cost associated with each product and service produced by the organization. The paper presents reasons for applying Activity-Based Costing in healthcare management.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 221-229